Alternatives to free molecular halogens as chemoselective reactants: Catalysis of organic reactions with reusable complexes of halogen metal salts - Rossi, Laura Isabel (2012)
Organometallic complexes of halogen metallic salts have been used as catalysts in different organic reactions, mainly the oxidation of organic compounds. Their use has not only allowed the reduction of the amounts of catalyst (since they can be reused) but also a lower generation of by-products and wastes. The different reaction media developed through the research were analyzed by several green parameters and the best results were obtained with complexes that have cyclodextrins as organic ligands. The proposed methodology is an alternative to use of molecular halogen as oxidant or catalyst when halogens are significant chemoselective reactants.